Uncovering the hidden meaning: an analysis of the performance structure and social meaning of the salonreng dance in the cultural context of Makassar - Linda, Johar; Indriyani, Putri Dyah; Djarot, Rachmat (Pascasarjana Institut Seni Indonesia Surakarta, 2024)
The Salonreng dance represents the cultural identity of the Makassar tribe. Despite its rich cultural significance, Salonreng dance is rarely witnessed and in demand by the public, as well is a lack of deep understanding of the meaning and values contained in Salonreng dance. This study aims to analyze the performance structure and social meaning of Salonreng dance better to understand its role in the cultural context of Makassar. The research method used is qualitative with an ethnocoreological approach, considering the cultural setting of the Salonreng dance. Direct observation was carried out by attending ritual activities; selected informants included actors, panrita (ritual leaders), dancers, pinati (ritual equipment organizers), local artists, and traditional leaders. Data collection was carried out through documentation of Salonreng dance performances in the form of ritual videos, books, and journals. The study results show that the Salonreng dance is an important element of Makassar's cultural heritage, which has high aesthetic, social, and spiritual value. The findings include Salonreng dance movements, criteria for dancers who are considered spiritually clean, accompanying musicians, audiences, dancers' clothing, dance floor patterns, and the transformation of the performance venue. The contribution of this research includes the enrichment of academic literature and the provision of research methodologies that can be used as a reference that supports the preservation and development of the Salonreng dance so that it becomes an important part of Makassar's cultural heritage and develops in the future.